Tunable Photoluminescence via Thermally Evaporated ZnS Ultra Thin Films - Urakawa, Yoshifumi; Gleason, Karen K. (Journal of Coating Science and Technology, 2014)
ZnS thin films have been deposited by thermal evaporation at various deposition rates. By controlling the deposition rate, the position of the maximum in the photoluminescence spectra could be easily tuned from 2.9 to 2.0 eV, which produced a corresponding change in the emission color. The optical and morphological characteristics of the ZnS thin films were measured. The photoluminescence spectra had broad peaks, suggesting a distribution of ZnS nanocrystallites dimensions. Nanocrystallites dimensions were in the range of 1 nm to 3 nm via TEM analyses. The changes in optical properties were potentially attributable to the lattice defects of ZnS crystals, including Schottky defects and the substation of sulfur atoms by oxygen atoms. The color of the resulting light emission was obtained by controlling the deposition rate of ZnS.